A three-season comparison of match performances among selected and unselected elite youth rugby league players - Waldron, M.; Worsfold, P. R.; Twist, C.; Lamb, K. (Journal of Sports Sciences, 2014)
This study compared technical actions, movements, heart rates and perceptual responses of selected and unselected youth rugby league players during matches (under-15 to under-17 age groups). The players` movements and heart rates were assessed using 5 Hz Global Positioning Systems (GPSs), while their technical actions were analysed using video analysis. The maturity of each player was predicted before each season for statistical control. There were no differences (P > 0.05) between selected and unselected players in the under-15 or the under-17 age group for any variables. However, in the under-16 age group, the selected players (57.1 ± 11.9 min) played for longer than the unselected players (44.1 ± 12.3 min; P = 0.017; ES = 1.08 ± CI = 0.87), and covered more distance (5181.0 ± 1063.5 m cf. 3942.6 ± 1108.6 m, respectively; P = 0.012; ES = 1.14 ± CI = 0.88) and high-intensity distance (1808.8 ± 369.3 m cf. 1380.5 ± 367.7 m, respectively; P = 0.011; ES = 1.16 ± CI = 0.88). Although successful carries per minute was higher in the selected under-15 age group, there were no other differences (P > 0.05) in match performance relative to playing minutes between groups. Controlling for maturity, the less mature, unselected players from the under-16 age group performed more high-intensity running (P < 0.05). Our findings question the use of match-related measurements in differentiating between selected and unselected players, showing that later maturing players were unselected, even when performing greater high-intensity running during matches.